EFEK DISINSENTIF PROGRAM RASKIN DAN PENGARUHNYA TERHADAP TRANSFER PANGAN ANTARGENERASI - Rasyid, Mohtar (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2012)
The objective of this research was to investigate disincentive and crowding-out effect food aid program (public transfer) in household level. Beside the humanitarian roles, there are widespread sceptisms of food assistance regarding its possible influence on disincentive to work and on crowding out of private transfer (inter-household or intergeneration transfer). Based on Indonesia Family Life Survey data and using instrumental variables approach, this paper estimates disincentive effect and crowding out effect âRice Program for Poor Familiesâ (Raskin) on intergenerational food transfer (child to parents transfer). This research observe significant negative impact on total household income. The decline in income mostly happened through a reduction in head household worker. The paper also find indication of crowding out relation between private and public transfers. It suggests that the Indonesian government should have designed its public transfer scheme carefully in order to improve the effectiveness and efficiency of its social safety net programs.